2003
DOI: 10.1007/s11746-003-0844-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of soy lecithins on vegetable oil stability and their synergism with tocopherols

Abstract: The antioxidant effect of lecithins was tested on several oils and fats varying in FA composition and tocopherol content. Standard lecithins, when added at a level of 1% w/w, exhibited a good protective effect against oxidation. This effect was observed to depend on the phospholipid content of the tested lecithins and the FA composition of the tested oils. Better results were obtained with lecithin samples containing high proportions of PC and PE. Indeed, the main antioxidant mechanism of lecithins was due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
99
0
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 12 publications
8
99
0
5
Order By: Relevance
“…fluids, which could be attributed to increasing dietary tocopherol intake, which was at least doubled when SL was added at 1%. Thus, the improvements in semen quality could be attributed to increasing oxidative stability (Scholfield, 1981;Judde et al, 2003;Ulkowski et al, 2005;Wang and Wang, 2008), a neuroprotective effect (Aabdallah and Eid, 2004), decreasing cellular damage (AST and ALT) and TBARS while increasing GSH, SOD, GST and GPx (Das and Vasudevan, 2006;Das et al, 2007). These enhancements were accompanied by better reproductive performance (conception rate) and litter size up to weaning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fluids, which could be attributed to increasing dietary tocopherol intake, which was at least doubled when SL was added at 1%. Thus, the improvements in semen quality could be attributed to increasing oxidative stability (Scholfield, 1981;Judde et al, 2003;Ulkowski et al, 2005;Wang and Wang, 2008), a neuroprotective effect (Aabdallah and Eid, 2004), decreasing cellular damage (AST and ALT) and TBARS while increasing GSH, SOD, GST and GPx (Das and Vasudevan, 2006;Das et al, 2007). These enhancements were accompanied by better reproductive performance (conception rate) and litter size up to weaning.…”
Section: Discussionmentioning
confidence: 99%
“…SL was also shown to decrease hepatic cellular damage and improve oxidative stability, and exerted neuroprotective activity through its antioxidant action (Aabdallah and Eid, 2004;Das and Vasudevan, 2006;Das et al, 2007;Wang and Wang, 2008). The effect of the antioxidant properties of lecithin could be attributed to the synergistic influence between amino-alcohol phospholipids and g-and d-tocopherols (Judde et al, 2003). Therefore, the aim of this study was to investigate the effect of SL supplementation on semen quality, blood testosterone concentration, blood and seminal plasma biochemistry including antioxidant status and fertility traits.…”
Section: Introductionmentioning
confidence: 99%
“…Judde et al 22 suggested that PC, PE and PS increased vegetable oil stability because their phospholipids had metal-chelating properties. In this study, metal ions in fi sh fi llets may be chelated by administrated soybean phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Zambiazi and Pryzybylski (1998) reported that the addition of 3% or more phospholipids to vegetable oil was effective. Judde et al (2003) showed that the addition of 1% soybean phospholipids inhibited oxidation in various oils, such as rapeseed, sunflower, soybean, walnut, palm, and fish oil, by measuring rancimat induction time (110℃) and peroxide value (40℃). The antioxidative mechanisms of phospholipids have been proposed to be due to the amino function of PC, PE and PS, which have been shown to have metal-chelating properties (Judde et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Judde et al (2003) showed that the addition of 1% soybean phospholipids inhibited oxidation in various oils, such as rapeseed, sunflower, soybean, walnut, palm, and fish oil, by measuring rancimat induction time (110℃) and peroxide value (40℃). The antioxidative mechanisms of phospholipids have been proposed to be due to the amino function of PC, PE and PS, which have been shown to have metal-chelating properties (Judde et al, 2003). Kashima et al (1991) and Hamilton et al (1998) reported that soybean PC and soybean PE increased the oxidative stability of soybean oil.…”
Section: Discussionmentioning
confidence: 99%